ANTI-ACNE ACTIVITY OF ACETONE EXTRACT OF PLUMBAGO INDICA ROOT - SK, GUPTA; P, MANDAL (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The aim of the present study was to investigate the effect of priming with exogenous sources of calcium ion and nitric oxide on the antioxidant activity, antidiabetic activity, and related phenolic contents along with the histochemical status of fenugreek sprouts. Methods: The fenugreek seeds were primed with calcium chloride (CC), calcium chelator ethylene glycol-bis (2-aminoethylether) -N, N, NÂ´, N tetra acetic acid (EG), sodium nitroprusside (SNP) and 2-(4-carboxyphenyl) -4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (CP) and germinated for 72 hrs. The sprout extracts were investigated for their antioxidant potential by 2,2-diphenyl-1-picrylhydrazyl, 2,2â€²-azino-bis-3-ethylbenzthiazoline-6sulfonic acid, reducing power as well as beta-carotene bleaching assays along with in vitro antidiabetic activity by Î±-amylase and Î±-glucosidase inhibition. Along with this, phytochemicals such as phenolics, flavonoids, and carotene content were also estimated, and the histochemical detection of reactive oxygen species in roots was performed. Results: The results demonstrated that the seeds pre-treated with CC and SNP showed enhanced antioxidant as well as antidiabetic potential over control; on the other hand, their action was reversed by their antagonists, EG, and CP. A similar trend was observed in the phytochemical contents of the sprouts. Furthermore, it was evident from the histochemical detection of H 2 O and superoxide localization as well as lipid peroxidation and plasma membrane integrity that the exogenous supply of calcium ion and nitric oxide exhibited protective role in the germinating seedlings. Conclusions: The study suggests the active involvement of the signal molecules, Ca 2 , and nitric oxide in signaling pathways associated with related phenolic compounds and oxidative stress management. 2+ Keywords: Antidiabetic, Antioxidant, Calcium ion, Germination, Histochemical localization, Phenolics, Nitric oxide, Trigonella foenum-graecum.